74 Paramedics' experiences of administering fascia iliaca compartment block to patients with suspected hip fracture. (16th April 2018) - Evans, B; Brown, A; Bulger, J; Fegan, G; Ford, S; Guy, K; Jones, S; Keen, L; Pallister, I; Rees, N; Russell, I; Seagrove, A; et al.
Abstract : Aim: Pre-hospital pain management for hip fracture is inadequate, with risk of complications, particularly from morphine. Fascia Iliaca Compartment Block (FICB) is used in hospital. The RAPID trial tested feasibility of paramedics administering FICB to patients with suspected hip fracture at the scene of injury. Method: We held three focus groups with 11 paramedics serving one hospital, audio-recorded with participants' consent. Two researchers, one paramedic and one lay member conducted thematic analysis of interview transcripts. Results: Respondents believed FICB was a suitable intervention for paramedics to deliver, aligning with their routine practice and within people's capabilities to administer. They said it took up to 10 min longer than usual care to deliver, in part due to nervousness and unfamiliarity with a new procedure. They praised the training provided but said they were anxious about causing harm by injecting into the wrong location. Reported challenges related to the emergency context: patients often waited many hours for ambulance arrival; they sometimes needed to be moved from awkward locations which exacerbated pain; family and neighbours were present as paramedics administered treatment. Although uncertain whether FICB reduced patients' pain more effectively than other pain relief options, respondents believed it was safer for elderly people. Conclusion: Paramedics are willing and able to administer FICB to patients with suspected hip fracture before ambulance transport to hospital. Feasibility study findings will inform a research proposal for a definitive multi-centre trial of paramedic administered prehospital FICB. Conflict of interest: None Funding: None